Preliminary investigation concept - Botayev, Murod (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
Comments are made in this article to thedefinition of the preliminaryinvestigation concept institute,the views of various scholars inthis area are studied and analyzed